Advances in extracellular vesicle experimentation in the context of skeletal growth - Jose Marchan (2026)
Although the molecular pathways regulating chondrocyte proliferation and differentiation have been extensively studied, the contribution of extracellular vesicles (EVs) to skeletal growth remains incompletely understood. EVs are nanoparticles that mediate intercellular communication in health and disease. Within the growth plate, matrix vesicles (MVs) have long been recognised for their role in initiating mineralisation; however, their broader functions to the wider EV landscape remain poorly defined.In this thesis, therefore, we set out to develop fundamental and robust EV-based technologies for applications in skeletal biology. First, we designed a robust and scalable protocol for the production and isolation of chondrocyte-derived EVs from ATDC5 cells before and during mineralisation, providing a physiologically relevant platform to obtain functional chondrocyte-derived EVs for subsequent mechanistic studies. Second, we investigated the intrinsic effects of dynamin inhibition, a typical target on EV uptake studies, on longitudinal bone growth. Our findings indicate that the inhibitor (dynasore) modulates bone growth depending on the dosage, promoting at low concentrations while suppressing it at high doses. Interestingly, the epiphyseal cartilage of bones with enhanced growth showed a high extracellular matrix (ECM) accumulation, highlighting a previously underappreciated role of the ECM in regulating skeletal elongation. Third, we developed a bioinformatics pipeline, BioProEV, to address the challenge of missing values in EV proteomic datasets derived from mass spectrometry. By using this novel framework, we were able to impute missing values from two different EV populations: foetal bovine serum-EVs and bovine milk-EVs, while preserving meaningful information for downstream functional analyses. Fourth, we mapped the human growth plate using a spatially resolved molecular atlas, demonstrating that resting zone chondrocytes are heterogeneous and include subpopulations exhibiting features of cellular quiescence, consistent with stem cell-like behaviour. To further validate these observations, we developed a highly reproducible protocol to obtain growth plate-MVs, which allowed us to identify sphingomyelin synthase 2 (SGMS2) as a new hypertrophic zone marker enriched within growth plate-derived MVs. Importantly, functional analyses demonstrated that SGMS2 contributes directly to MV-mediated mineralisation, providing a mechanistic link between SGMS2-associated skeletal disease and impaired endochondral ossification.List of scientific papersI. A protocol to differentiate the chondrogenicATDC5 cell-line for the collection of chondrocyte-derived extracellular vesicles. Jose G. Marchan-Alvarez, Loes Teeuwen, Doste R. Mamand, Susanne Gabrielsson, Klas Blomgren, Oscar P. B. Wiklander, Phillip T. Newton. Journal of Extracellular Biology (2023); 3(9), e70004. https://doi.org/10.1002/jex2.70004II. Dynamin inhibitor dynasore modulates longitudinal bone growth in a hormetic manner. Jose G. Marchan-Alvarez, Sanya Koikkara, Ruihan Zhou, Amal Nazaraliyev, Oscar P. B. Wiklander, Phillip T. Newton. BMC Biology 2026;24(1). https://doi.org/10.1186/s12915-026-02687-4III. BioProEV: a bioinformatics pipeline for biologically-relevant handling of missing values in the analysis of extracellular vesicles by mass spectrometry. Pâmella Miranda, Jose G. Marchan-Alvarez, Annemarijn Offens, Ruihan Zhou, Mathieu Y. Brunet, Loes Teeuwen, Maria Eldh, Susanne Gabrielsson, and Phillip T. Newton. Journal of Extracellular Biology (2026); 15:5:e70150. https://doi.org/10.1002/jex2.70150IV. Human growth plates house resting zone sub-populations with features of quiescent stem cells. Mahtab Avijgan†, Ana R.L. Perez†, Leire Alonso Galicia†, Jose G. Marchan-Alvarez‡, Laura Sudupe‡, Ruihan Zhou, Amal Nazaraliyev, Žaneta Andrusivová, Ludvig Larsson, Pâmella Miranda, Doste R. Mamand, Yunhan Zhao, Farasat Zaman, Hong Qian, Klas Blomgren, Felipe Prosper, Oscar P.B. Wiklander, Jesper N. Tegner, Joakim Lundeberg, Lars Sävendahl, Reza Mirzazadeh, David Gomez-Cabrero, Phillip T. Newton. Bone Research https://doi.org/10.1038/s41413-026-00564-y† Indicates equal first authorship. ‡ Indicates equal second authorship.